(untitled) (CIPEEX, 2025)
This open, single-center clinical trial aimed to evaluate the effects of pulsed electromagnetic field (PEMF) muscle stimulation technology. Sarcopenia is a condition characterized by a decrease in muscle mass and strength, as well as functional decline in older adults. The study included 30 older adults individuals who did not practice any type of physical activity, who underwent 12 PEMF sessions on the lower limbs (LL), in addition to resistance exercises for the upper limbs (UL). The PEMF protocol was performed for 30 minutes on the rectus-femoris and gastrocnemius muscles simultaneously. The volunteers underwent clinical evaluations and assessment tests, such as dynamometry, to measure lower limb muscle strength before and after the application of the PEMF protocol. The results showed that there was a strength gain of approximately 30%, which is quite significant considering the gradual loss of strength in the older adult population. This study reinforces the relevance and effectiveness of pulsed electromagnetic fields in generating contraction and, consequently, muscle strength in older adults with muscle strength loss and sarcopenic older adults.